Virtuous spaces, virtual places: institutionalizing values on ethical consumerism in the Indian toy industry through field-configuring events - Saheli Nath (Future Business Journal)
Abstract Focusing on India's toy industry, this study investigates how field-configuring events facilitate the institutionalization of ethical consumerism in emerging markets. Through virtual ethnographic analysis of the First India Toy Fair 2021, we examine how digital platforms enable institutional change processes. Drawing on institutional theory, we identify three key mechanisms through which the fair shaped ethical consumption practices: normative space creation, regulatory framework development, and cultural-cognitive meaning making. The fair served as a platform where stakeholders collectively defined ethical practices, negotiated quality standards, and legitimated traditional production methods within contemporary sustainability discourse. Our findings reveal how virtual field-configuring events can transcend geographical boundaries to enable broader participation in institutional change processes, while also highlighting the complex interplay between traditional craft values and modern market demands. The study demonstrates how traditional practices can provide templates for sustainable production while meeting contemporary consumer expectations. These insights contribute to understanding how ethical markets are moralized in emerging economies and how virtual spaces can support the preservation and evolution of traditional craft sectors.